1992
DOI: 10.1007/bf00052564
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the superoxide radical scavenger superoxide dismutase, and of the hydroxyl radical scavenger mannitol, on reperfusion injury in isolated rabbit hearts

Abstract: Hydroxyl radical formation, secondary to superoxide radical generation, has been advocated as the actual mechanism of oxygen radical-mediated damage in biological systems. The present study was designed to compare the efficacy of administration of the hydroxyl radical scavenger mannitol vs. that of the superoxide radical scavenger superoxide dismutase (SOD) in reducing myocardial reperfusion injury, and to test whether combined treatment with both agents would confer better tissue protection compared with eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…One explanation for this protective action of mannitol is that this agent serves as a scavenger of hydroxyl radicals (43)(44) and thereby reduces oxidant-induced peroxidative damage (45). However, we observed that mannitol increased the generation of ROS in LLC-PK 1 cells.…”
Section: Discussionmentioning
confidence: 53%
“…One explanation for this protective action of mannitol is that this agent serves as a scavenger of hydroxyl radicals (43)(44) and thereby reduces oxidant-induced peroxidative damage (45). However, we observed that mannitol increased the generation of ROS in LLC-PK 1 cells.…”
Section: Discussionmentioning
confidence: 53%
“…Nevertheless, it should be considered that glutathione can also scavenge ROS and that CS contains ROS (39). However, 4 diverse ROS scavengers (mannitol, ascorbic acid, lycopene, and β-carotene), which target different oxygen species, including superoxide, hydroxyl radical, peroxyl radicals, sulphur radicals, nitrogen-oxygen radicals, and singlet oxygen (40)(41)(42)(43), failed to affect the Ca 2+ response or the bronchoconstrictor effect of CSE. H 2 O 2 , which produces ROS, has been recently reported to stimulate TRPA1 (25).…”
Section: Discussionmentioning
confidence: 99%
“…As both NAC and MESNA also bear antioxidant properties, their efficacy might result from scavenging ROS contained in CSE. However, five different ROS scavengers (mannitol, uric acid, ascorbic acid, lycopene, and ␤-carotene), which target various oxygen species, including superoxide, hydroxyl radical, peroxyl radicals, sulphur radicals, nitrogenoxygen radicals, and singlet oxygen (2,11,32,45), failed to reduce IL-8 release induced by CSE in both SAEC and NHLF cultures. Therefore, given also the lack of effect of H 2 O 2 on IL-8 release, we conclude that ROS species contained in CSE play a minor role (if any) in directly eliciting IL-8 release in the experimental conditions here adopted.…”
Section: Discussionmentioning
confidence: 99%